Efeito da vitrificação na resistência de união de um material adesivo à zirconia (Y-TZP) - Dreyer, Júlia Willers (2020)
Aim: Yttrium-stabilized polycrystalline tetragonal zirconia (Y-TZP) has been widely used in dentistry due mainly to its mechanical properties. However, due to its polycrystalline characteristic and absence of a vitreous phase, the adhesive cementation of Y-TZP can still be considered a challenge. Therefore, the present study aimed to compare the surface treatment considered the gold standard described by the manufacturer (sandblasting with aluminum oxide and the use of adhesive containing MDP) with experimental surface treatments based on vitrification techniques (covering with vitreous ceramic or glaze). Among the specific objectives, the surface pattern of the samples was qualitatively assessed by scanning electron microscopy (SEM) and by X-ray dispersive energy spectrometry (EDX). The bond strength of the samples to the micro shear in 24h and after 12 months of simulated aging was also evaluated, as well as the fracture pattern of the samples. Conclusion: In the first article, it was possible to conclude that the use of vitreous covering or glaze ceramics for Y-TZP substrate vitrification seems to be suitable for adhesive cementation. There was evidence of vitreous elements embedded into zirconia even after prolonged exposure to hydrofluoric acid. In the second article, despite the satisfactory results in the immediate analysis of the group covered with vitreous ceramic, it was concluded that the sandblasting technique with Al2O3 could still be considered the gold standard, since it is time-saving and simpler to perform, supported by literature, less expensive, and less technique sensitive than the inner coating with a ceramic veneer; in addition, it requires fewer additional materials.